TINGKAT KEPUASAN PELANGGAN DI KATERING MARDIKA JAKARTA - Suryawati Mahdalena; Nova Eviana; Rudhi Achmadi (LPPM Universitas Asa Indonesia, 2020)
The background of this research was conducted because many entrepreneurs started businesses in the culinary sub-sector. Culinary development, especially in the catering sector, have a positive impact on society. The purpose of this study was to determine the level of customer satisfaction at Mardika Catering and the efforts required to increase customer/consumer satisfaction. The population of this research are the customers of Mahardika Katering. The sampling technique by saturated method where all customers as respondents excluding the trial one for instrument testing. Data collection technique used by sensus method using questionnaire, during March to May 2020. Data analysis by descriptive and qualitative. The conclusion of this study is that the highest value is found in indicators of interest in returning to visit and willingness to recommend and for conformity with expectations is still below average that need to be upgraded to compley with customers satisfaction.